Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I need to find a solution to the differential following equation:

$y'=\frac {y} {3x-y} $.

I tried to use use some kind of substitution, but I didn't manage to solve it.

Any suggestion\help?

Thanks a lot!

share|improve this question
    
You lost me here $y'=\frac {y} {3x-y} \Rightarrow 3x-y^2=y$. Maybe this is using techniques I'm not familiar with, but this seems wrong. –  AlanSE Mar 23 '12 at 21:54
    
Sorry, my mistake. –  Jozef Mar 23 '12 at 22:04
    
Perhaps this. –  David Mitra Mar 23 '12 at 22:05
    
It seams that $y=ax$ could be a solution. –  martini Mar 23 '12 at 22:07

4 Answers 4

up vote 4 down vote accepted

Hint: Try $y=zx$. That will let you separate variables.

share|improve this answer
    
You mean the denominator is $3x-y^2$? I don't know, nonlinear equations are difficult. One might be able to come up with a special trick reducing to a Riccati, but a little scribbling got me nowhere. In the original problem, taking advantage of homogeneity was an automatic reflex. –  André Nicolas Mar 24 '12 at 16:06

We can transform this equation to linear differential equation.

$ \frac{dx}{dy}= \frac{3x}{y}-1 $

And integrating factor $\lambda=e^{{\int{\frac{-3}{y}dy}}}=y^{-3}$.

Then $ x=\frac{\int(-1)y^{-3}dy}{y^{-3}}$. Therefore $x=cy^{3}+\frac{y}{2}$.

share|improve this answer
    
If you care to, you can explicitly solve for $y$ in terms of $x$ when $c\geq0$. If $c=0$, then of course $y=2x$. If $c>0$, then the cubic formula yields $y=\sqrt[3]{ \frac{x}{2c}+\sqrt{\frac{x^2}{4c^2}+\frac{1}{216c^3}}}+\sqrt[3]{ \frac{x}{2c}-\sqrt{\frac{x^2}{4c^2}+\frac{1}{216c^3}}}$. –  alex.jordan Mar 24 '12 at 0:03

I followed $y=z.x$ transform and I got easily the general solution : $cy^3+y=2x$

$3cy^2y'+y'=2$

$(3cy^3+y)y'=2y$

$(3.(2x-y)+y)y'=2y$

$(6x-2y)y'=2y$

$(3x-y)y'=y$

$y'=\frac{y}{3x-y}$

If you cannot manage the y=z.x transform ,let me know.

share|improve this answer

$$ y' = \frac{y}{3x - y} = \frac{1}{\frac{3x}{y} - 1} $$

$$ \frac{y}{x} = v \Rightarrow y = vx \Rightarrow \frac{dy}{dx} = x \frac{dv}{dx} + v $$

$$ x \frac{dv}{dx} + v = \frac{1}{\frac{3}{v} - 1} = \frac{v}{3 - v} $$

$$ x \frac{dv}{dx} = \frac{v}{3-v} - v = \frac{v(v-2)}{3-v} $$

$$ \frac{(3-v)dv}{v(v-2)} = \frac{dx}{x} $$

$$ \Rightarrow \int \frac{(3-v)}{v(v-2)} \ dv = \int \frac{dx}{x} = \ln x + c $$

$$ \frac{(3-v)}{v(v-2)} = \frac{A}{v} + \frac{B}{v-2} $$

$$ \Rightarrow A(v-2) + Bv = 3 - v $$

$$ v = 2 \Rightarrow B = \frac{1}{2} $$

$$ v = 0 \Rightarrow A = -\frac{3}{2} $$

$$ \Rightarrow \int \frac{(3-v)}{v(v-2)} \ dv = -\frac{3}{2} \int \frac{1}{v} \ dv + \frac{1}{2} \int \frac{1}{v-2} \ dv = \frac{1}{2} \ln(v-2) - \frac{3}{2} \ln v = \ln x + c $$

$$ v = \frac{y}{x} \Rightarrow \frac{1}{2} \ln \left(\frac{y}{x}-2 \right) - \frac{3}{2} (\ln y - \ln x) = \ln x + c $$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.